Design of Health Department E-Archive - Pipit Pujiarti (SAINTEKBU, 2023)
Currently, one of the problems that occurs at the Indramayu District Health Office is that the process of searching for data stored in folders is taking too long because you have to go through one sheet at a time. The data sought is also not always complete or even lost. This is because the data has not been stored in a computerized database. The purpose of this research is to create a filing information system for the Indramayu District Health Office, which will change the filing process that was previously still manual to be computerized. The formulation of the research problem is how to design a filing information system for the Indramayu District Health Office and create an appropriate application program. At the implementation stage, this system will use the PHP programming language and MySQL as the database. Based on these objectives,